Migraine and Gallbladder Motility - Doina, Georgescu; Oana, Ancusa; Liviu-Andrei, Georgescu; Daniela, Reisz (European Scientific Journal, ESJ, 2016)
Introduction Five (5) hydroxitryptamine (5-HT) selective receptor agonists (triptans) were reported to have gastric motor effects. However, less is known about their role on gallbladder (GB) motility. Aim: Assessment of GB motility in patients treated with orodispersable triptans for migraine’s attacks. Patients and Methods: Out of 112 patients with various forms of migraine who required triptans while having headache attacks, followed-up in our ambulatory service, we have selected 30 patients diagnosed with mild to moderate migraine. These patients include: 15 with aura (3 men, 12 women, mean age=41,8±16,42 years) and 15 without aura (2 men, 13 women, mean age=47,73±18,50 years). Consequently, they had an ejection fraction (EF) of GB which is less than 60% (previously measured in intercritic period by elipsoid ultrasound Dodds method). Furthermore, no record of prokinetic or proton pump inhibitor treatments, gastric surgery, gallstones, collagen or thyroid disease, diabetes mellitus, cardiac, liver, kidney failure or cancer disease was recorded. The measurements of the GB were made while having a migraine attack, before and in every 15 minutes till 90 minutes. This was after receiving 5 mg of orodispersable zolmitriptan. Results: There are no statistical significant difference between initially EF of the two groups (p=0,8190). Patients with migraine with aura showed a mean EF=42,53±4,31% before therapy. After therapy, the mean EF improved significantly: 48,80±3,23% (p=0,0001). Patients having migraine without aura displayed an initially mean EF=42,53±3,27%. In addition, they had a very statistically significant response to therapy with important improvement of EF to 61,47±7,07% (p<0,0001). Conclusions: 5HT selective receptor agonists increased GB motility, in migraine attacks with a response above the cut-off range of EF, in patients having migraine without aura.